Determinants of Risk Behaviour of Banana Cultivators: A Case Study in Jaffna Peninsula of Sri Lanka - Umashankar, K.; Mythreaji, K. (Sri Lanka Agricultural Economics Association, 2015)
It is widely recognized that a high level of uncertainty exemplifies the lives of farm households in developing countries. Jaffna district, located in the Northern part of Sri Lanka, has been ravaged by war in the last three decades, continuously experiences a variety of uncertainties. Hence, the researchers have taken effort to (i) find out the determinants of risk aversion attribute of banana cultivators in the Jaffna peninsula and (ii) propose policy recommendations to strengthen risk aversion attribute of banana cultivators in Jaffna peninsula. Stratified purposive random sampling method was used to draw the samples from the population. A pre-tested structured questionnaire was employed obtaining an effective sample size of 204. Structural equation model was used to analyze the risk aversion with livelihood approach. The results revealed that the six endogenous latent variables such as income and food access, assets, social safety net, adaptive capacity, stability and access to public services have positive significant effect on the risk aversion attribute of peninsular banana cultivators. The resulted second level of interactions between endogenous latent variable and the measurable variables revealed that food access score, dietary diversity index, durable index, land ownership, frequency of assistance, employment ratio, coping strategy index, crop diversification, educational level of household head, access to communication facilities, and physical access to quality drinking water, have a positive significant impact on risk aversion while education system stability, access to electricity and access to input market revealed a significant negative impact on the risk aversion of banana cultivators of the Jaffna peninsula. Thus it can be recommended that the government and non-governmental organizations should arrange training classes, seminars, and extension services which help the cultivators to obtain an adequate knowledge about market and climate uncertainties, natural disasters, continuous damage, coping strategies and risk aversion mechanisms.
Keywords: Risk aversion; Banana farming; Structural equation model; Jaffna Peninsula; Sri Lanka